The effect of transcranial random noise stimulation on the movement time and components of noise, co-variation, and tolerance in a perceptual-motor task - Fatemeh Salehi; Mohammadreza Doustan; Esmaeel Saemi (Scientific Reports)
Abstract There exist numerous factors that contribute to the amplification of errors and complexity in motor processes, among which variability and noise are particularly noteworthy. Transcranial random noise stimulation (tRNS) has been proposed as a potential means of enhancing motor performance by modulating excitability in the motor cortex. This study aimed to examine the role of the concomitant administration of tRNS with training in enhancing the performance measures of movement time, noise, covariation, and tolerance in the acquisition of a perceptual-motor task. This study enlisted a cohort of 30 healthy male adults (mean age: 22.62 ± 3.83 years) who were randomly assigned to three distinct groups. The participants executed the specified motor task during three sequential phases, namely, the pre-test, intervention, and post-test phases. Statistical analyses showed that training with tRNS has a significant effect on noise cost, co-variation, and movement tolerance (p ≤ 0.05). In addition, tRNS improved the function of the sensorimotor wave (p ≤ 0.05). Moreover, the results indicate that tRNS elicited a significant reduction in both spatial error and movement execution time, (p ≤ 0.05). The study’s findings indicate that a mere three training sessions leveraging tRNS may suffice in diminishing the spatial error; nevertheless, a higher number of training sessions is required to alleviate the temporal error.